Penyebab Keterlambatan Kelengkapan Dokumen dan Kualifikasi Penyedia Jasa Alih Daya pada Kereta Api Logistik - Amelia, Nabilla Rizki; Ricardianto, Prasadja; Fitrina, Rehani; Adi, Erman Noor; Wahyuni, Endang (Institut Transportasi dan Logistik Trisakti, 2024)
There are still obstacles in the outsourcing service procurement system faced by PT. Kereta Api Logistik, especially in the procurement of goods and services, delays in completing documents, lack of documents uploaded by providers. Aims of this research are; to analyze the main root causes and factors for delays in completeness, documents and provider qualifications in the smooth process of procuring outsourcing services. Another objective is what actions or solutions are carried out by PT. Kereta Api Logistik in overcoming the smooth procurement of outsourcing services. The method used in this research is Pareto 80/20 and Fishbone analysis, by conducting interviews with nine employees and field research. The results of the study found several obstacles, namely selective differences in perceptions, lack of user calculations regarding budget requirements at the beginning of the year, because there was no socialization before procurement began to vendors who would be partners, lack of coordination between users and people in the charge of the area or area regarding requirement specifications in the field, and the document is not approved by the board of directors, it changes. From this research the next procurement system can be improved.